Improving energy efficiency for fishing vessels using two-pitch propellers - Co Tan Anh Vu; Phan Van Hung; Dang Dinh Chien; Vu Dang Thai; Pham Ky Quang (Journal of International Maritime Safety, Environmental Affairs, and Shipping)
Energy efficiency and CO2 emission reduction technologies play a vital role in the “Net-zero” strategy of the United Nations. Enhancing the power and fuel efficiency of waterway vehicles, particularly those with powerful propulsion systems, is becoming a major worldwide concern in the fight against emissions. Propeller boss cap fin systems are only one of the many ways that propulsion systems’ efficiency can be increased. Unfortunately, because they are either expensive or too difficult to install and operate, they are not appropriate for Vietnam’s offshore fishing fleets. In this study, a two-pitch propeller model was proposed, considering the operating characteristics of offshore fishing vessels with two stages: the free-running and the trawling stage. The hydrodynamic features of the fixed propeller and the propeller’s two pitches were analyzed using the numerical approach with a diameter of 1 m; a speed of 629 rpm; expanded area ratio of 0.5. The outcomes demonstrated that the two-pitch propeller’s overall efficiency with a pitch-blade of 0.6, consisting of the efficiency in working freely and the stage of trawling, is higher than the fixed propeller’s efficiency of the same size. Two-pitch propellers are seen as a significant step in bettering the planning of national fishing vessels’ emission reduction strategies.